Kebijakan Penegakan Hukum Pidana Terhadap Sponsor Perjudian Online Terhadap Tim Esports Di Indonesia - Wibowo, Fadhil Rahadyan; Putri, Nella Sumika; Atmaja, Budi Arta (Justisia: Jurnal Ilmu Hukum, 2025)
The Esports industry in Indonesia is experiencing significant growth with large economic contributions, but raises legal issues related to the involvement of sponsors from online gambling companies. Although Article 27 paragraph (2) of the Electronic Information and Transaction Law (ITE Law) expressly prohibits gambling, sponsorship practices continue without effective enforcement. This research aims to analyse the application of criminal law against online gambling sponsorship of Esports teams in Indonesia, identify obstacles to law enforcement, and formulate effective criminal law policy strategies. This article is a legal research that not only conducts studies related to laws and regulations, literature, and legal documents, but is also complemented by empirical data through in-depth interviews with the DIY Police Cyber Directorate, Bandung District Attorney, Ministry of Communication and Digital, and the Indonesian Esports Executive Board, as well as direct observation in the field. The results show that to date there has been no investigation, prosecution or conviction of Esports teams receiving online gambling sponsorship. The main obstacles include difficulties in proving the element of intent (mens rea), lack of formal evidence, limited digital forensic facilities, low public legal awareness, and the normalisation of gambling culture in the Esports community. Normatively, the legal basis is adequate, but implementation constraints make the penal path difficult to apply. Therefore, non-penal strategies in the form of legal education, increasing digital literacy, strengthening internal regulations, and cross-sector collaboration need to be optimised, while criminal law functions as an ultimum remedium.